Cho (a-b)(b-c)(c-a) = (a+b)(b+c)(c+a) .Chứng minh a^2b + b^2c+ c^2a+ abc=0 - H
Ta có:\(\left(a-b\right)\left(b-c\right)\left(c-a\right)=\left(a+b\right)\left(b+c\right)\left(c+a\right)\)
\(\Leftrightarrow\left(a-b\right)\left(b-c\right)\left(c-a\right)-\left(a+b\right)\left(b+c\right)\left(c+a\right)=0\)
\(\Leftrightarrow\left(a^2c-ac^2+bc^2-b^2c+ab^2-a^2b\right)-\left(2abc+ac^2+a^2c+b^2c+bc^2+a^2b+ab^2\right)=0\)
\(\Leftrightarrow a^2c-ac^2+bc^2-b^2c+ab^2-a^2b-2abc-ac^2-a^2c-b^2c-bc^2-a^2b-ab^2=0\)
\(\Leftrightarrow-2a^2b-2b^2c-2ac^2-2abc=0\)
\(\Leftrightarrow-2\left(a^2b+b^2c+c^2a+abc\right)=0\)
\(\Leftrightarrow a^2b+b^2c+c^2a+abc=0\left(đpcm\right)\)